Automatic Bayesian polarity determination. Issue 1 (20th April 2016) - Pugh, D.J.; White, R.S.; Christie, P.A.F.
Abstract: The polarity of the first motion of a seismic signal from an earthquake is an important constraint in earthquake source inversion. Microseismic events often have low signal-to-noise ratios, which may lead to difficulties estimating the correct first-motion polarities of the arrivals. This paper describes a probabilistic approach to polarity picking that can be both automated and combined with manual picking. This approach includes a quantitative estimate of the uncertainty of the polarity, improving calculation of the polarity probability density function for source inversion. It is sufficiently fast to be incorporated into an automatic processing workflow. When used in source inversion, the results are consistent with those from manual observations. In some cases, they produce a clearer constraint on the range of high-probability source mechanisms, and are better constrained than source mechanisms determined using a uniform probability of an incorrect polarity pick.